PENGELOLAAN KEUANGAN DESA DI DESA CILOGRANG KECAMATAN CILOGRANG KABUPATEN LEBAK Berdasarkan Peraturan Bupati Lebak Nomor 9 Tahun 2016 - Jumarta Jumarta; Ade Hadiono Ade Hadiono (LPPM STIA Banten, 2018)
This study aims to find out how village financial managers are in Cilograng Village, Cilograng District, Lebak Regency based on the Regent Regulation Number 9 of 2016. This research uses a descriptive qualitative method, namely describes village financial management with the principle of Accountable, Transparent, Accurate Time, and Participative. The results of this study indicate that for management village finances in Cilograng Village, Cilograng District, Lebak Regency physically, interviews, and broad observations have revealed financial management in accordance with the applicable legal basis, namely Lebak Regent Regulation number 9 year 2016. This can be seen from the results of the inspection of Cilograng sub-district officials who stated that there were no problems in financial management in Cilograng Village. However The Cilograng Village Community Institution still needs coaching and guidance related to Village financial management so that they play a better role in planning, implementation and accountability.